The receding horizon of informality in WTO meetings. (16th March 2017) - Lamp, Nicolas
Abstract : The essay starts from the observation that attempts to formalize negotiations in the World Trade Organization (WTO) have consistently spawned new forms of informality, such as the holding of meetings as 'chairperson's consultations' which do not require the adoption of an agenda, or the emergence of new types of 'unofficial' documents. The essay sketches the resulting layers of formality/informality and attempts to account for the survival of informality in the WTO. The most commonly offered explanation for the persistence of informality in WTO negotiations is that it serves to facilitate and disguise the exercise of power. The essay argues instead that formal and informal meetings serve essentially different functions. Informality can provide opportunities for productive interventions, alliances, and performances that are precluded in more formal settings. Gradations of formality/informality offer different avenues for WTO Members to talk to each other and to their domestic and international audiences.